The Influence of Profitability, Dividend Policy, and Institutional Ownership as Moderating Variables on Firm Value - GANAWATI, Nengah; PRATIWI, Ketut Winda; SUDARMINI, Ketut; SARIANI, Ketut (Journal of Governance, Taxation and Auditing, 2024)
This study aims to analyze the effect of profitability and dividend policy on firm value with institutional ownership as a moderating variable. The study was conducted in the financial sector listed on the Indonesia Stock Exchange for the 2018-2020 period. The research method uses a quantitative approach with a purposive sampling technique, resulting in a sample of 22 companies. Data were analyzed using Moderated Regression Analysis (MRA) to test the hypothesis. The results of the study indicate that profitability and dividend policy have a positive and significant effect on firm value. In addition, institutional ownership is proven to strengthen the positive relationship between profitability and dividend policy with firm value. This finding supports the signaling theory which states that profitability and dividend policy provide positive signals to investors regarding the company's prospects. This study contributes to investors and management in decision making, by emphasizing the importance of good corporate governance to increase firm value. The practical implications are that companies are advised to increase profitability, stable dividend policies, and involve institutional ownership to minimize agency conflicts and maximize firm value.